Children’s Participation in the Design of Ludic Spaces in Early Childhood Education Schools (Olhar de Professor, 2023)
This article proposes some reflection upon the relationship between architecture and early childhood education, mainly regarding the children’s participation in the design of spaces. We introduce the educational thoughts of authors who conceived space as an education environment. In the study on the architecture of school buildings, we emphasize external spaces and the importance of the children’s participation in the creation of such environments. Finally, we analyze the experience of the project of building a model road for toy cars in a municipal early childhood education school (EMEI - Escola Municipal de Educação Infantil) in Belo Horizonte as part of an action in the qualification of students from the Education Course in the Teaching Initiation Scholarship Institutional Program, PIBID/UFMG. The new environment was integrated to the children’s ludic activities and broadened the possibilities of external use of the school space. It also enabled a strong case study to be considered in the education of new teachers.
Keywords: Early childhood education.; School architecture.; Education Professional Qualification.